Studies on Hydroxyl Radical Formation and Correlated Photoflocculation Process Using Degraded Wood Leachate as a CDOM Source - Sun, Luni; Mopper, Kenneth (Frontiers in Marine Science, 2016)
In this study, we examined hydroxyl radical (•OH) formation with respect to photoreactivity of colored dissolved organic matter (CDOM), the Fenton reaction, and photoflocculation using leachate from decaying wood. The relationship between •OH photoproduction rate and leachate optical properties (UV-visible absorption and fluorescence excitation-emission matrices (EEMS)) was studied during irradiation using a UV solar simulator. The results showed that the •OH photochemical formation rate is strongly related to humic-like fluorescence as characterized by parallel factor analysis (PARAFAC), and that these fluorescence components are more photolabile than most of the other CDOM components. Fourier transform infrared spectroscopy (FT-IR) indicated the photodegradation of lignin-related structures. To examine the role of iron and •OH in the photoflocculation process, Fe speciation (particulate Fe, organically-complexed Fe(II), organically-complexed Fe(III), free Fe(II), and free Fe(III)) were measured in the leachate samples amended with Fe. The addition of Fe accelerated •OH production substantially, and Fe was photochemically cycled between Fe(II) and Fe(III). The photodegradation of iron complexing ligands appears to play an important role in DOM photoflocculation.